AUTOPHAGY IN LUNG CANCER - Jaboin, Jerry J. (2009)
Lung cancer is the leading cause of cancer-related deaths worldwide. The relatively poor cure rate in lung cancer patients has been associated with a resistance to chemotherapy and radiation that is at least in part related to defects in cellular apoptotic machinery. Exploitation of another form of cell death, autophagy, has the capacity to improve the therapeutic gain of current therapies. In an effort to develop novel treatment strategies to enhance the therapeutic ratio for lung cancer, we wish to better understand the role of autophagic cell death for the sensitization of lung cancer. This text reviews the most up to date protocols and techniques for the study of autophagic cell death in lung cancer models. Others may use these techniques as a framework for study within their experimental models.